Correlates of Mental Health in Survivors of Colorectal Cancer: The Influence of Individual, Family, and Community Level Factors - Shelby C. Borowski; Elizabeth J. Siembida; Katrina Nygren; Keith M. Bellizzi (Journal of Behavior Therapy And Mental Health, 2016)
An often neglected factor in the examination of the mental quality of life of survivors of colorectal cancer is the role of family and community level resources and support. The aim of this study was to develop a deeper understanding of the influence of family and community level resources over and above previously examined mental health variables. A survey-based pilot study was conducted with 101 colorectal cancer survivors. Four multiple linear regression models were developed to examine the associations between demographic, health-related, individual psychosocial, family and community level factors, and specific dimensions of mental quality of life (measured using the mental health subscales of the SF-12). In addition to examining all of the correlates of mental quality of life, the unique role of family and community level factors over and above previously examined factors was examined. Analyses found that family and community level factors, as a whole, explained a significant portion of the variance in role emotional health, mental health, and social functioning over and above demographic, health-related, and individual psychosocial factors. Family cohesion was a significant, unique predictor of role limitations due to mental health, and family and community social support was a significant, unique predictor of role limitations due to mental health and overall mental health. These results suggest the potential importance of considering family and community level resources when conducting research and designing interventions to improve mental quality of life in colorectal cancer survivors.
Keywords: Colorectal Cancer